2006
DOI: 10.1523/jneurosci.3907-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Musical Experience on Different Components of MEG Responses Elicited by Sequential Piano-Tones and Chords

Abstract: Magnetoencephalographic (MEG) studies have revealed enhancement of neural activity of the N1m response of auditory evoked fields in long-term trained musicians, reflecting neuroplastic modification of the representation of the auditory cortex. In contrast, the amplitude of the P2 response of auditory evoked potentials is modified by musical experience, with no alteration of N1. Here, we performed a comprehensive MEG study using stimulation of successive musical-instrument tones to examine how the neural activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 53 publications
14
69
2
1
Order By: Relevance
“…Many of these responses, including auditory "middle latency" responses (~19-80 ms) and the longer latency N1/N1m (100 ms, N1m designating the magnetic counterpart of the electrical N1), N1c (140 ms), P2 (180 ms), and N2m (250 ms) responses, have been shown from electromagnetic studies to be enhanced in young and adult musicians compared to non-musicians (Middle latency: Schneider et al 2002;Shahin et al 2004;N1c: Shahin et al, 2003;N1m: Pantev et al 1998;N2m: Fujioka et al 2006;P2: Shahin et al, 2003P2: Shahin et al, , 2004P2: Shahin et al, & 2005P2m: Shahin et al, 2005;Kuriki et al 2006). Enhancement of the middle latency P50 response in musicians has been shown to parallel an increase of gray matter in Heschl's gyrus, suggesting an enhanced neural population in trained musicians (Schneider et al 2002(Schneider et al & 2005.…”
Section: Introductionmentioning
confidence: 98%
“…Many of these responses, including auditory "middle latency" responses (~19-80 ms) and the longer latency N1/N1m (100 ms, N1m designating the magnetic counterpart of the electrical N1), N1c (140 ms), P2 (180 ms), and N2m (250 ms) responses, have been shown from electromagnetic studies to be enhanced in young and adult musicians compared to non-musicians (Middle latency: Schneider et al 2002;Shahin et al 2004;N1c: Shahin et al, 2003;N1m: Pantev et al 1998;N2m: Fujioka et al 2006;P2: Shahin et al, 2003P2: Shahin et al, , 2004P2: Shahin et al, & 2005P2m: Shahin et al, 2005;Kuriki et al 2006). Enhancement of the middle latency P50 response in musicians has been shown to parallel an increase of gray matter in Heschl's gyrus, suggesting an enhanced neural population in trained musicians (Schneider et al 2002(Schneider et al & 2005.…”
Section: Introductionmentioning
confidence: 98%
“…Prior investigations into the neurological effects of musical experience have mainly focused on the neural plasticity of the cortex Trainor et al, 2003;Kuriki et al, 2006;Rosenkranz et al, 2007;Lappe et al, 2008), but recent studies have shown that neural plasticity also extends to the subcortical auditory system. This is evidenced by enhanced auditory brainstem response (ABR) phase locking to fundamental pitch and the harmonics of the fundamental and by earlier response latencies in subcortical responses to musical, linguistic, and emotionally valent nonspeech sounds (Musacchia et al, 2007(Musacchia et al, , 2008Wong et al, 2007;Strait et al, 2009) (for review, see Kraus et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies employing electroencephalography (EEG) or MEG have provided evidence that instrumental tones elicit increased responses compared to sine-wave tones in nonmusicians, too (Lutkenhoner, Seither-Preisler, & Seither, 2006;Meyer, Baumann, & Jancke, 2006;Shahin, Roberts, Pantev, Trainor, & Ross, 2005). Nevertheless, the direct contrast of musicians to nonmusicians has been shown to reveal increased amplitudes in several auditory-evoked potential (AEP) components or components of its magnetic equivalent, the auditory-evoked field (AEF) (Kuriki, Kanda, & Hirata, 2006;Shahin et al, 2005;Shahin, Bosnyak, Trainor, & Roberts, 2003, but see Lutkenhoner et al, 2006 for counterevidence). These effects mainly pertain to the AEP/AEF 1 negativity N1 and the positivity P2.…”
Section: Introductionmentioning
confidence: 99%